Lessons from 20 Years of Capacity Building for Health Systems Thinking. Issue 3 (2nd July 2016) - Reich, Michael R.; Yazbeck, Abdo S.; Berman, Peter; Bitran, Ricardo; Bossert, Thomas; Escobar, Maria-Luisa; Hsiao, William C.; Johansen, Anne S.; Samaha, Hadia; Shaw, Paul; Yip, Winnie
Abstract: In 2016, the Flagship Program for improving health systems performance and equity, a partnership for leadership development between the World Bank and the Harvard T.H. Chan School of Public Health and other institutions, celebrates 20 years of achievement. Set up at a time when development assistance for health was growing exponentially, the Flagship Program sought to bring systems thinking to efforts at health sector strengthening and reform. Capacity-building and knowledge transfer mechanisms are relatively easy to begin but hard to sustain, yet the Flagship Program has continued for two decades and remains highly demanded by national governments and development partners. In this article, we describe the process used and the principles employed to create the Flagship Program and highlight some lessons from its two decades of sustained success and effectiveness in leadership development for health systems improvement.